(untitled) ((PJHAS) PUSA Journal of Hospitality and Applied Sciences, 2025)
Background: The hospitality industry’s commitment to sustainability relies not only on implementation but also on guest awareness and engagement. This study evaluates the degree of guest knowledge about sustainable hotel practices and identifies which practices are most and least recognized. It further explores the sources through which guests learn about these initiatives and examines the correlation between their awareness and willingness to support such efforts. Objectives: The study aimed to assess guests’ awareness of sustainable practices, determine the most and least known initiatives, identify key information sources, and analyse the relationship between knowledge and willingness to engage in sustainability. Methodology: A descriptive research design was employed using a structured questionnaire distributed via convenience sampling. Responses were collected from 385 hotel guests across India. Data analysis through SPSS included descriptive statistics, one-sample t-tests, and Spearman’s rho correlation. Results: Recycling and waste management programs (mean=3.92) and the use of eco-friendly toiletries (mean=3.80) were the most recognized practices, while energy-efficient HVAC systems (mean=3.35), sewage treatment plants (mean=3.45), and towel reuse programs (mean=3.34) were least known. All practices showed statistically significant mean scores above the hypothesized moderate level of 3 (p < 0.001). Social media emerged as the most common information source, followed by hotel websites and in-room materials. However, 17.9% of respondents reported no awareness of any practices, and staff communication was the least reported source. A positive and statistically significant correlation (ρ=0.499, p < 0.001) was found between guest knowledge and their willingness to support sustainable initiatives. Conclusion: The study emphasizes the need for improved communication and educational strategies within hotels to bridge awareness gaps. Enhancing visibility of sustainability efforts through digital and direct engagement can boost guest participation and contribute to broader environmental goals.